Laboratory animal medicine - Fox, James G.; Anderson, Lynn C.; Otto, Glen M.; Pritchett-Corning, Kathleen R.; Whary, Mark T.; American College of Laboratory Animal Medicine (Amsterdam : Elsevier : Academic Press, 2015)
Laboratory Animal Medicine, Third Edition, is a fully revised publication from the American College of Laboratory Medicine's acclaimed blue book series. It presents an up-to-date volume that offers the most thorough coverage of the biology, health, and care of laboratory animals. The book is organized by species, with new inclusions of chinchillas, birds, and program and employee management, and is written and edited by known experts in the fields. Users will find gold-standard guidance on the study of laboratory animal science, as well as valuable information that applies across all of the biological and biomedical sciences that work with animals.
E. Animal Transportation Association and International Air Transport AssociationIV. Hazardous Substances; A. Biohazards; B. Chemical Agents; C. Radioactive Materials and Radiation-Emitting Equipment; V. Nucleic Acid and Nanomaterial Research Guidelines; References; 3 Biology and Diseases of Mice; I. Introduction; A. Origin and History; B. Genetic History; C. Genetics; D. Breeding Systems; E. Induced Mutant Mice (Genetically Engineered Mice); 1. Engineered Endonuclease Technologies; F. Nomenclature; G. Housing, Husbandry, and Nutrition; 1. Housing and Husbandry; 2. Nutrition; II. Biology.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Laboratory animals; Laboratory animals -- Diseases; Laboratory animals -- Law and legislation; Animals, Laboratory; Laboratory animals -- Diseases; Laboratory animals; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Laboratory animals; Laboratory animals -- Diseases; Laboratory animals -- Law and legislation; Electronic books